2008
DOI: 10.1111/j.1464-5491.2007.02315.x
|View full text |Cite
|
Sign up to set email alerts
|

The association of genetic variants in Krüppel‐like factor 11 and Type 2 diabetes in the Japanese population

Abstract: AimsKrüppel-like factor 11 (KLF11) is a transcriptional factor of the zinc finger domain family that regulates the expression of insulin. In North European populations, its common functional variant Q62R (rs35927125) is a strong genetic factor for Type 2 diabetes (P = 0.00033, odds ratio for G allele = 1.29, 95% CI 1.12–1.49). We examined the contribution of KLF11 variants to the susceptibility to Type 2 diabetes in a Japanese population.MethodsBy re-sequencing Japanese individuals (n = 24, partly 96), we scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…A variant of the promoter of KLF11 has also been linked to insulin sensitivity in a Danish population (167). However, similar studies failed to demonstrate an association of any genetic variants of KLF11 with type 2 diabetes in Japanese or native American populations (236, 260, 418). …”
Section: Chapter Iv: Organ-based Functions In Physiology and Pathophymentioning
confidence: 93%
“…A variant of the promoter of KLF11 has also been linked to insulin sensitivity in a Danish population (167). However, similar studies failed to demonstrate an association of any genetic variants of KLF11 with type 2 diabetes in Japanese or native American populations (236, 260, 418). …”
Section: Chapter Iv: Organ-based Functions In Physiology and Pathophymentioning
confidence: 93%
“…Thus, KLF11 is a candidate diabetogenic gene in Japanese. Tanahashi et al reported identification of eight variants, but were unable to find any missense mutation or association of common KLF11 variants in late-onset Type2 diabetes in 1818 Japanese subjects [26].…”
Section: Discussionmentioning
confidence: 99%
“…No association of KLF11 variants with T2DM was found and no haplotypes were found to show susceptibility to T2DM. We examined one variant, rs4073397, located 21 kb upstream from the coding region and outside of the LD block of the KLF11 region, that shows a marginal association with T2DM in Japanese [26], but we could not replicate the association in this study with power similar to that of the former report (P = 0.268 and 0.576 for allele and genotype analysis, respectively; OR 1.2; RAF 0.5; α = 0.05; 1-β = 63.9%).…”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, alterations in the coupling of KLF11 to HDACs due to variations in the sequence of the KLF11 promoter and protein have been found in selected human populations affected by type 2 diabetes mellitus (T2DM). 12-15 Noteworthy, in spite of its strong-association with diabetes, the role of KLF11 in inflammatory responses that affect the cardiovascular system remains to be addressed. Consequently, the current study sought to define whether KLF11 influences the EC response to pro-inflammatory stimuli.…”
Section: Introductionmentioning
confidence: 99%